Green one-pot synthesis of N-based heterocycles involving o-phenylenediamine. (2021) - Verma, Monika; Sharma, Renu; Bharti, Ruchi; Tangri, Amanpreet
Abstract: Multicomponent reactions have achieved significant applications in synthetic organic chemistry for the synthesis of heterocyclic compounds by using a variety of precursors. One such precursor is o -Phenylenediamine (OPDA) which easily condensed with different carbonyl moieties. In the past few years a great deal of work has been done with this magical compound and the aim of this study is to provide an insight in that work which explored OPDA by using green techniques.